Marked Regression of Left Ventricular Hypertrophy after Outflow Desobliteration in HOCM - Zisis Dimitriadis; Frank van Buuren; Nikola Bogunovic; Dieter Horstkotte; Lothar Faber (Case Reports in Medicine)
We present an HOCM patient in whom marked regression of left ventricular hypertrophy occurred within two years following outflow desobliteration by percutaneous septal ablation. Maximum wall thickness (initially documented by both echo and MRI) decreased from 34 mm to 22 mm (followup by echo only due to presence of the ICD), crossing the threshold value of 30 mm which was one of the risk markers that had triggered the primary prophylactic ICD implantation in this case prior to septal ablation.